2022
DOI: 10.31004/jkt.v3i2.4400
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Risiko Kejadian Hipertensi Pada Remaja

Abstract: Sustainable Development Goals (SDGs) are a world agreement for a long period by maximizing resources as the potential of each country and taking into account sustainable development for the well-being of human, environmental, social, and other parts of life in the world. Health is currently the main problem faced by Indonesia, especially the problem of the double burden of disease, where infectious diseases are still the main focus that must be addressed. However, on the other hand, non-communicable diseases (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Residents with low education are associated with low awareness of healthy living behaviors and inadequate access to healthcare facilities, thereby increasing the risk of unhealthy lifestyles. 18,19 Based on previous studies, it was found that smoking behavior has a significant relationship with hypertension in adolescents and severe stress in adolescents. [20][21][22] Smoking by adolescents is a risk factor for dietary mistakes, poor oral health, and more dynamic damage to teeth, which may result in pain and tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Residents with low education are associated with low awareness of healthy living behaviors and inadequate access to healthcare facilities, thereby increasing the risk of unhealthy lifestyles. 18,19 Based on previous studies, it was found that smoking behavior has a significant relationship with hypertension in adolescents and severe stress in adolescents. [20][21][22] Smoking by adolescents is a risk factor for dietary mistakes, poor oral health, and more dynamic damage to teeth, which may result in pain and tooth loss.…”
Section: Discussionmentioning
confidence: 99%